Imidazolium Ionic Liquids as Designer Solvents Confined in Silica Nanopores - Ana-Maria Putz; Adél Len; László Trif; Zsolt Endre Horváth; László Almásy (Gels, 2022)
Composite silica xerogels were prepared via acid catalysed sol–gel route using tetraethoxysilan (TEOS) as silica precursor, and 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM][BF4] or 1-butyl-3-methylimidazolium chloride [BMIM][Cl] ionic liquids, used simultaneously as co-solvents, catalysts and pore templates, at various IL-to-silica ratios. Morphology of the xerogels prepared using the different IL templating agents were investigated using scanning electron microscopy (SEM), nitrogen sorption and small angle neutron scattering (SANS). The thermal behavior of the composites was analyzed by thermal gravimetry, whereas the compositions were checked by infrared spectroscopy and EDX. The differences in the morphology and thermal behavior of the composites due to the different IL additives were revealed.